Pengembangan Media Pembelajaran Video Animasi Interaktif Menggunakan Aplikasi Powtoon pada Materi Bioteknologi Kelas XII - Syafri Ramadhan (Universitas Pendidikan Ganesha, 2024)
Packet books, LKS (student worksheets) and whiteboards are still learning media that are often used, while the percentage from preliminary study results shows that 96.8% of students are more interested and enthusiastic if interactive animated videos are used in the learning process. This research aims to determine the design, feasibility and practicality of developing interactive animated video learning media. This research uses Research and Development research using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. This research used rating scale calculations for feasibility testing by one media expert and one material expert and Likert scale calculations for practicality testing by one biology teacher and 15 students. The media expert feasibility test results, if calculated in percentage terms, get a score of 93.75% which is categorized as very feasible. The results of the material expert feasibility test, if calculated in percentage terms, get a score of 84.38% which is categorized as very feasible. The results of the teacher practicality test, if calculated in percentage terms, get a score of 96.67% which is categorized as very practical. The results of the students' practicality test, if calculated in percentage terms, get a score of 90.10% which is categorized as very practical. So, it can be said that the development of interactive animated video learning media using the Powtoon application in class XII biotechnology material that has been developed is very feasible and very practical when used in the learning process.